The Free Tissue Transfer–Masquelet–Reamer-Irrigator-Aspirator Bone Graft Orthoplastic Approach for Lower Extremity Reconstruction. Issue 6 (15th April 2022) - Maruccia, Michele; Vicenti, Giovanni; Carrozzo, Massimiliano; Caizzi, Gianni; Di Summa, Pietro G.; Moretti, Biagio; Giudice, Giuseppe; Elia, Rossella
Abstract : Summary: The management of critical-sized bone and soft-tissue defects of the lower extremity poses unique challenge to reconstructive surgeons. The aim of this article is to present the authors' current orthoplastic approach for the management of extended (more than 6 cm) osteocutaneous defects of the lower extremity, based on a sequential combination of two stages: free flap for soft-tissue coverage and the Masquelet technique (first step) followed by reamer-irrigator-aspirator cancellous bone graft and definitive osteosynthesis (second step). This study was a single-center observational retrospective review of prospectively collected data. Adult patients (>18 years of age) with segmental bone loss of the lower extremity caused by acute trauma (Gustilo type IIIB fracture) or nonunion (septic/aseptic) who were treated with the free flap for soft-tissue coverage–Masquelet technique–reamer-irrigator-aspirator approach between January of 2017 and December of 2020 were included. Time of consolidation and early and late complications were recorded. A total of 11 patients (nine male patients and two female patients) with a mean age of 45.8 years were identified. The average bone gap length (standard deviation) was 87.3 (24.9) mm. An anterolateral thigh flap was harvested in all cases. The average duration of the first stage (i.e., time from antibiotic cement spacer placement and free flap to time of bone grafting) was 50.4 days (range, 40 to 62 days). Bone consolidation was achieved in all cases after an average period (standard deviation) of 20.4 (3.3) weeks, with acceptable functional outcomes. The free flap for soft-tissue coverage–Masquelet technique–reamer-irrigator-aspirator approach could be considered a viable option in patients with segmental critical-sized bone defects associated with a large soft-tissue deficit of the lower extremity. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, IV.